Milk production and composition of “Beni Arouss” North Moroccan local goat - El Otmani S.; Hilal B.; Chentouf M. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
The aim of the study was to investigate the milk potential of ‘Beni Arouss‘ North Moroccan local goat, under intensive and extensive nutritional regimes. During two years (2011-2012), milk yield was measured once per month and milk samples were collected during the lactation period. Solid non-fat content, fat, protein, and lactose were analysed by infrared method. Does produced more (P < 0.01) milk under the intensive, compared to the extensive nutritional regime (597.9 ± 264.35 g per day versus 504.2 ± 189.59 g per day). Milk from intensive production system was higher protein 4.32% and fat 5.87% content (P < 0.001) than extensive production system, which had 3.9% in protein and 3.36% in fat. In contrast lactose content was significantly higher in extensively reared (4.61% vs 4.42%, P < 0.01). No differences were observed for defatted dry extract between production systems. In conclusion, the local goat “Beni Arouss” produces more milk in the intensive system that is richer in fat and protein compared to extensive system.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)